ANALISIS TERHADAP PRAKTIK KECURANGAN KUOTA HAJI DALAM KACAMATA HUKUM EKONOMI SYARIAH - Taopik Paturohman; Achmad Ru'yat Alfarizi; Rizki Akmal; Jaenudin Jaenudin; Dian Herdiana (CV. Denasya Smart Publisher, 2025)
This study examines the controversy surrounding the distribution of Hajj quotas allocated by Saudi Arabia to Indonesia in 2024, focusing on alleged allocation irregularities currently being investigated by the Corruption Eradication Commission (KPK), from the perspective of Sharia Economic Law. The main issue is the tension between Law No. 8 of 2019, which stipulates a regular Hajj quota of 92% and a special Hajj quota of 8%, and the discretionary policy of the Ministry of Religious Affairs through a ministerial decree dividing the additional quota of 20,000 into 50:50 (regular and special). Using a qualitative method with a juridical-empirical approach, this study analyses field data related to the argument of the Sharia-based logistical limit of the Mina area (maa baynal jabalin). The results of the study show that logistically, this policy is based on the principles of Maslahah Mursalah and Hifz an-Nafs to avoid extreme crowding in the regular Mina tents. However, in terms of positive law, this action violates regulations and, in terms of Islamic economic law, contains elements of distributive injustice and Tuhmah (suspicion) due to a lack of transparency that has the potential to lead to risywah (bribery) for commercial gain.